Przemilczenia w kulturze. Przyczynek do historii Sylvii Likens - Rzepkowska, Aleksandra (Zeszyty Wiejskie, 2016)
Sylvia Marie Likens was an American murder victim from Indiana. She was tortured to death by a housewife – Gertrude Baniszewski, Gertrude’s children, and other young people from their neighborhood in Indianapolis. Sylvia was the third child of carnival workers – Betty and Lester Likens. The Likens’ marriage was unstable and the family moved many times. Sylvia was often boarded out or forced to live with relatives while her parents were working. In the summer of 1965 16-year-old Sylvia and her a year younger sister Jenny, who was disabled from polio, were left in the care of the Baniszewski family three months before her death. The author of the article tells the story of Sylvia Likens and indicates different kinds of concealment practices which are essential elements of the crime. These social practices favored domestic violence against Sylvia. Therefore, they contributed largely to the extreme suffering, both physical and mental, and ultimately to the premature death of the girl.